Ensiklopedia olahraga Indonesia - Mulya, Andi. (Bandung : Angkasa, 2011)
Encyclopedia of sports.
jil. 1. A - I -- jil. 2. J - P -- jil. 3. R - Z.
Includes index.
Keywords: Sports -- Encyclopedias; Sports -- Indonesia -- Encyclopedias